(untitled) (Bangladesh Journal of Botany, 2020)
In order to increase the fertilizer use efficiency, the effects of different ratio of slow-release fertilizer, water retention agent and compound fertilizer in wheat production on senescence of flag leaf in winter wheat had been studied. The results showed that, water retaining agent 15 kg/ha with slow-release fertilizer 324 kg/ha and compound fertilizer 324 kg/ha (T2) effectively maintained the activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) activity and soluble protein content in wheat flag leaves after flowering, and reduced the malondialdehyde (MDA) content which could delay the flag leaves senescence and gain high yield in wheat.